Experimental and Numerical Study of Thermo-Hydraulic Performance of Circumferentially Ribbed Tube with Al2O3 Nanoﬂuid - M. Kh., Abdolbaqi; Nor Azwadi, Che Sidik; R., Mamat; Azmi, W. H. (Elsevier, 2015)
The mechanisms of heat transfer enhancement are used in many industrial applications. Therefore several techniques have been promoted to enhance heat transfer rate and to decrease the size and cost of equipment especially the heat exchangers. Heat transfer coefficient and pressure drop for Al2O3/water Nanofluid flow inside circumferential ribbed tubes with different rib dimensions have been determined numerically. The nanoparticle size is set equal to 13 nm and the volume fractions from 0% to 3% are used. The ribbed copper tubes tested in this investigation with inner diameter of 14.9 mm have the ranges: circumferential depth from 0.5 to 1.5 mm and axial pitch distance from 5 to 15 mm. The inlet temperature of turbulent nanofluid is 25 °C and the wall constant heat flux is 5,000 W/m2. The study is accomplished by means of Ansys Fluent code and its purpose involves into find arrangements and depth of ribs such to provide low pressure drops and high heat transfer coefficients in existence of water /Al2O3 nanofluids . Comparison of numerical data of circumferentially ribbed tubes with plain tube have shown that the heat transfer coefficient, quantified by means of Nusselt number increase from 92 to 621% and friction factor increase from 25 to 241% compared to those obtained in smooth tube depending on the circumferential geometric parameters, mass velocity and thermal conductivity of the working fluid.